Comprehensive evaluation and zoning study of potential geothermal water resources in Qinghai Province, northeastern margin of the Tibetan Plateau - Xie, Wenping; Lu, Rui; Liu, Bo; Zhu, Jinshou; Cai, Jinshou; Zhang, Deseng; Wang, Xianrong (Frontiers in Earth Science, 2026)
The geothermal resources in Qinghai Province are endowed with superior potential, yet overall exploration remains at a relatively low and spatially uneven level. Most sedimentary basins and structural fault zones within the province have not undergone systematic exploration, leading to relatively high exploration risks. To address this challenge, this study developed a novel semi-quantitative methodology that integrates basin heat storage and tectonic heat control theories, breaking through the traditional “heat-following” exploration paradigm. The study divides the province’s hydrothermal resources into 16 potential sedimentary basin (conductive-type) zones and 32 potential fault zones (mountain uplift convective-type). Based on genetic elements of “source-pathway-cap-reservoir-flow,” a multidimensional evaluation index system was established. Innovatively combining the analytic hierarchy process (AHP) and principal component analysis (PCA), this research quantitatively assessed the resource potential of each zone and classified the potential levels using the quartile method. By integrating the evaluation results from both approaches, a total of 32 geothermal resource prospective areas were delineated across the province, including 10 sedimentary basin-type and 22 fault zone-type areas. Building on this, and closely considering resource potential, population distribution, regional development plans, and preliminary environmental screening, 10 target areas were prioritized for early-stage exploration deployment. The research outcomes provide a systematic scientific basis for strategic planning and governmental decision-making regarding the exploration and development of geothermal resources in Qinghai Province.